Two copper(II)-bbtz modified Keggin and β-octamolybdate compounds captured in one-pot under hydrothermal conditions. Issue 7 (3rd April 2017) - Ying, Jun; Liu, Jia-Ni; Li, Ting-Ting; Tian, Yan; Ni, Huai-Ping; Ji, Xue-Bin; Liu, Guo-Cheng; Tian, Ai-Xiang
Abstract: Under hydrothermal conditions two compounds based on Keggin and β -octamolybdate, respectively, [Cu2 (bbtz)4 (SiMo12 O40 )] (1 ) and [Cu2 (bbtz)4 (Mo8 O26 )]1/2 ·H2 O (2 ) (bbtz = 1, 4-bis(1, 2, 4-triazol-1-ylmethyl)benzene), were synthesized in one-pot and characterized by single-crystal X-ray diffraction, elemental analyses, and IR spectroscopy. In compound1, two adjacent wave-like Cu II -bbtz lines are connected by SiMo12 anions and bbtz to generate a ladder-like chain. Adjacent chains share the same Cu II ions to build a three-dimensional (3-D) framework. In compound2, the β -Mo8 anions link Cu3 (bbtz)2 subunits alternately to form a one-dimensional (1-D) chain. These chains connect each other through sharing Cu II ions and a 3-D network is constructed. Moreover, we studied the electrocatalytic and photocatalytic activities of these two compounds. The results indicate that1 and2 show good electrocatalytic performance for the reduction of nitrite and bromate; they also exhibit photocatalytic properties for degradation of MB and RhB. Abstract :